Increased Anion Channel Activity Is an Unavoidable Event in Ozone-Induced Programmed Cell Death - Kadono, Takashi; Tran, Daniel; Errakhi, Rafik; Hiramatsu, Takuya; Meimoun, Patrice; Briand, Joël; Iwaya-Inoue, Mari; Kawano, Tomonori; Bouteau, François (PloS one, 2010)
Ozone is a major secondary air pollutant often reaching high concentrations in urban areas under strong daylight, high temperature and stagnant high-pressure systems. Ozone in the troposphere is a pollutant that is harmful to the plant. By exposing cells to a strong pulse of ozonized air, an acute cell death was observed in suspension cells of Arabidopsis thaliana used as a model. We demonstrated that O(3) treatment induced the activation of a plasma membrane anion channel that is an early prerequisite of O(3)-induced cell death in A. thaliana. Our data further suggest interplay of anion channel activation with well known plant responses to O(3), Ca(2+) influx and NADPH-oxidase generated reactive oxygen species (ROS) in mediating the oxidative cell death. This interplay might be fuelled by several mechanisms in addition to the direct ROS generation by O(3); namely, H(2)O(2) generation by salicylic and abscisic acids. Anion channel activation was also shown to promote the accumulation of transcripts encoding vacuolar processing enzymes, a family of proteases previously reported to contribute to the disruption of vacuole integrity observed during programmed cell death. Collectively, our data indicate that anion efflux is an early key component of morphological and biochemical events leading to O(3)-induced programmed cell death. Because ion channels and more specifically anion channels assume a crucial position in cells, an understanding about the underlying role(s) for ion channels in the signalling pathway leading to programmed cell death is a subject that warrants future investigation.